Physics of ferromagnetism - Chikazumi, Sōshin, 1922-2016 (International series of monographs on physics, 1997)
"This book is intended as a textbook for students and researchers interested in the physical aspects of ferromagnetism. The level of presentation assumes only a basic knowledge of electromagnetic theory and atomic physics and a general familiarity with rather elementary mathematics. Throughout the book the emphasis is primarily on explanations of physical concepts rather than on rigorous theoretical treatments which require a background in quantum mechanics and high level mathematics. The purpose of this book is to give a general view of magnetic phenomena, focusing its main interest at the centre of the broad field of ferromagnetism, ranging from theory to the engineering applications such as soft and hard magnetic materials and magnetic memories. Substantially different from the author's previous book Physics of Magnetism published in 1964, the present edition is neatly organized and includes more recent developments"--Provided by publiser